The Influence of Spiritual Intelligence, Emotional Intelligence and Intellectual Intelligence towards Student Learning Achievement - Taupik, Muhammad (Journal of English Language and Education, 2025)
This study investigates the influence of Spiritual Intelligence, Emotional Intelligence, and Intellectual Intelligence on students' English learning outcomes. The primary objective of this research is to determine the extent to which these three forms of intelligence influence students' academic performance in English, and to assess how strong the impact of each form of intelligence is on learning achievement. This study uses a survey method with correlational and regression analysis techniques to examine the relationships between the three independent variables—Spiritual Intelligence, Emotional Intelligence, and Intellectual Intelligence—and one dependent variable, English learning achievement. The key findings of this study reveal a significant simultaneous influence of Spiritual Intelligence, Emotional Intelligence, and Intellectual Intelligence on English learning achievement, with a Sig value of 0.000 and an F count of 43.27. These three intelligences together account for 60.3% of the variance in English learning achievement, while the remaining 39.7% is attributed to other factors not studied. Additionally, each form of intelligence individually shows a significant impact on learning achievement: Spiritual Intelligence (Sig = 0.000, t = 4.001), Emotional Intelligence (Sig = 0.001, t = 3.684), and Intellectual Intelligence (Sig = 0.001, t = 3.687). These findings suggest that enhancing Spiritual, Emotional, and Intellectual Intelligence can significantly improve students' academic performance in English.